2015
DOI: 10.17795/iji-22906
|View full text |Cite
|
Sign up to set email alerts
|

Fever of Unknown Origin in Children Aged Three Months to Fifteen Years

Abstract: Background: Fever of unknown origin (FUO) is defined as the presence of fever in a child for eight or more days that a careful history and physical examination and preliminary laboratory results failed to reveal the probable cause of the fever. The causes of FUO are different according to geographical regions and age. Objectives: The current study aimed to evaluate the common causes of childhood FUO in Zahedan, Iran. Patients and Methods:A six-year retrospective study was conducted on all admitted children age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…M. tuberculosis was detected in three patients (15.8% of the cases of infectious disease), which was similar to the results from previous studies in countries with a high prevalence of tuberculosis including Korea, China, Iran, and India1618). Chow and Robinson2) concluded that there was difference in the types of infections responsible for pediatric FUO between developing and developed countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…M. tuberculosis was detected in three patients (15.8% of the cases of infectious disease), which was similar to the results from previous studies in countries with a high prevalence of tuberculosis including Korea, China, Iran, and India1618). Chow and Robinson2) concluded that there was difference in the types of infections responsible for pediatric FUO between developing and developed countries.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, in Table 6, we only reviewed the data between 2000 and 2014 from various countries113141516171819202122). Although infectious disease still appears to be the most common cause of FUO in children, it would be interesting to assess for changes in the etiologies of FUO in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There is no widespread consensus on the definition of fever of unknown origin (FUO), and various definitions have been applied throughout the years (2,(10)(11)(12). Currently, fever in children is considered FUO after 8 or more days of febrile illness, when a careful and thorough history taking, physical examination, and laboratory workup failed to reveal a probable cause of the fever (7,9,13). If these criteria apply, but children have fever for less than 8 days, they are sometimes considered to have "fever without source" (FWS) (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…For example, is enteric fever caused by Salmonella sp (Plaza et al 2016). In General, the body's rectal temperature range between 36°C to 37.8 °C (Solimani et al, 2015). The American College of Critical Care Medicine, the International Statistical Classification of Diseases, and The Infectious Diseases Society of America Society of infectious diseases of the United States that can be described as fever if body temperature reaching 38.3°C or higher, i.e., just above the upper limit of normal human temperature.…”
Section: Introductionmentioning
confidence: 99%